Clonal Disemination of Klebsiella pneumoniae ST258 Harbouring KPC-2 in Argentina - Gómez, Sonia Alejandra (2011)
The present work describes the abrupt emergence of Klebsiella pneumoniae carbapenemase (KPC) and characterizes the first 79 KPC-producing enterobacteria from Argentina (isolated from 2006 to 2010). The emergence of blaKPC-2 was characterized by two patterns of dispersion: the first was the sporadic occurrence in diverse enterobacteria from distant geographical regions, harbouring plasmids of different incompatibility groups and blaKPC-2 in an unusual genetic environment flanked by ISKpn8-DblaTEM-1 and ISKpn6-like. blaKPC-2 was associated with IncL/M transferable plasmids; the second was the abrupt clonal spread of K. pneumoniae ST258 harbouring blaKPC-2 in Tn4401a.